Determination of acoustic fields in industrial rooms - PIECHOWICZ, Janusz (Archives of Acoustics, 2007)
Problems of determination of acoustic field parameters in industrial rooms by means of testing and modelling this field with an application of geometric acoustics are presented in the paper. Next stage of the study was utilisation of inverse methods for assessment acoustic parameters of machines in industrial conditions. The development of inverse methods accompanied by the geometric methods of estimation the sound signal propagation in rooms allows to localise complex sound sources more effectively. These achievements are related to the development of calculating tools and techniques and multichannel acquisition systems of measured data.